ANALISIS SENGKETA TRANSFER PRICING ATAS PEMBAYARAN ROYALTI KEPADA PIHAK AFILIASI TERKAIT PEMANFAATAN KNOW HOW - Ainun Uswatul Khasanah; Jasman Jasman (Jurnal Akuntansi dan Pajak, 2024)
This research discusses transfer pricing policies regarding differences in views between Tax Authorities and Taxpayers on royalty payments made to affiliates in connection with the utilization of Intangible Property in the production process at manufacturing companies through a case study of Decision Number PUT-010351.15/2018/PP/M.XIIB Year 2020. This study uses a qualitative approach with a descriptive design. The results of this research indicate that affiliate transactions in the form of royalty payments cannot be automatically considered as part of transfer pricing practices (profit shifting). Royalty payments to affiliates are considered reasonable or permissible if they have met the arm’s lenght principles. However, if the royalty payment transactions do not reflect the arm’s lenght principles and the utilization of intangible property cannot be proven, then payments to affiliates may be considered as tax avoidance practices. The key point in assessing whether there is tax avoidance practice is the need for preliminary testing and transfer pricing examination analysis regarding the utilization of intangible property in accordance with the prevailing tax regulations in Indonesia.